Visible Spectrophotometric Determination of Terazosin Hydrochloride from Bulk Drug and Formulations - S. Sarsambi, Prakash; Kapse, G.K.; Appala Raju, S. (Asian Journal of Chemistry, 2010)
Two simple and sensitive spectrophotometric methods are developed for the quantitative estimation of terazosin hydrochloride. In the first method, the drug solution was reacted with p-dimethyl amino benzaldehyde (PDAB) to form Schiff base which has maximum absorption at 410 nm. The yellow coloured chromogen was stable for more than 1h. Beer's law was obeyed in the concentration range of 2–10 mcg/mL. In the second method the drug solution was reacted with bromo cresol purple in the presence of acid phthalate buffer (pH 2.2) to form yellow coloured complex with absorption maximum at 423 nm. The yellow coloured complex was stable for more than 2 h. Beer's law was obeyed in the concentration range of 10–60 mcg/mL.